An Ex vivo Model of an Oligodendrocyte-directed T-Cell Attack in Acute Brain Slices - Göbel, Kerstin (J Vis Exp, 2015)
Death of oligodendrocytes accompanied by destruction of neurons and axons are typical histopathological findings in cortical and subcortical grey matter lesions in inflammatory demyelinating disorders like multiple sclerosis (MS). In these disorders, mainly CD8(+) T-cells of putative specificity for myelin- and oligodendrocyte-related antigens are found, so that neuronal apoptosis in grey matter lesions may be a collateral effect of these cells. Different types of animal models are established to study the underlying mechanisms of the mentioned pathophysiological processes. However, although they mimic some aspects of MS, it is impossible to dissect the exact mechanism and time course of ‘‘collateral’’ neuronal cell death. To address this course, here we show a protocol to study the mechanisms and time response of neuronal damage following an oligodendrocyte-directed CD8(+) T cell attack. To target only the myelin sheath and the oligodendrocytes, in vitro activated oligodendrocyte-specific CD8(+) T-cells are transferred into acutely isolated brain slices. After a defined incubation period, myelin and neuronal damage can be analysed in different regions of interest. Potential applications and limitations of this model will be discussed.